Determination of biology pre-service teachers readiness to implement ICT skills and collaboration activities in teaching and learning in Kaduna State Nigeria (IR) - Francisca, Adeddeji Damilola (2018)
This study investigated the readiness of Nigerian biology pre-service teachers to implement 21st century skills specifically ICT skill and collaboration activities in teaching and learning (TnL). The respondents comprised of 123 Biology pre-service teachers in two higher institutions in Kaduna state, Nigeria. Their readiness was assessed using questionnaire with four-point Likert scale and interview sessions. The validity of the questionnaire was approved and the Cronbachs alpha reliability coefficient was 0.95. Descriptive statistics, ANOVA and correlation was used to analyze quantitative data while responses from the interview sessions were described by grouping and explaining the pre-determined themes. Findings showed that Nigerian biology pre-service teachers are ready to implement ICT skill in TnL in terms of confidence, awareness and motivation, perception, knowledge and training. However, they were not ready in terms of ICT equipment. Findings also showed that equipment were required if they must conduct collaboration activities effectively in their TnL. There was no statisical significant difference between male and female biology pre-service teachers to implement ICT skill and collaboration activities. Positive significant correlation existed between their readiness to implement ICT skill and collaboration activities. In conclusion, findings from this study offered hopeful suggestions and clues that biology pre-service teachers were ready in terms of their confidence, awareness and motivation, perception, knowledge and training to implement ICT skill and collaboration activities in their TnL processes. The study serves as a foundation for further studies to be conducted in other fields and on readiness of Nigerian pre-service teachers to implement other 21st century skills.